Evidence of transplacental transmission of equine piroplasms Theileria equi and Babesia caballi in an Italian breed mare - Bartolome Del Pino, Leticia E; Meana, Aranzazu; Zini, Maurizio; Cersini, Antonella (Folia parasitologica, 2023)
Equine piroplasmosis (EP) is a vector borne disease caused by apicomplexans protists Babesia caballi (Nuttal et Strickland, 1910) and Theileria equi (Laveran, 1901). Carrier mares may transmit the infection transplacental resulting in neonatal piroplasmosis or abortions. This event has been described for T. equi by several authors over the world, but no evidence for B. caballi has been reported in Europe. In this study, vertical transmission for both parasites in an Italian breed mare has been confirmed using molecular and microscopic tools. Transplacental transmission is an underestimated problem mainly in endemic areas as it not only contributes to the spread and maintenance of the infection, but also produces significant economic losses.
Keywords: Cattle; Animals; skot; babezióza; Female; Theileria; Theileriasis; ženské pohlaví; vertical transmission; nemoci koní; Italy; těhotenství; theilerióza; Itálie; koně; abortions; Horses; Babesiosis; polymerase chain reaction; Babesia; serological assays; zvířata; Pregnancy; Horse Diseases